2022
DOI: 10.1007/s13364-022-00642-6
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a commercial lure to attract red fox

Abstract: In camera trap studies, attractants may be used to increase detection probabilities of wildlife, which may help to improve estimates of abundance and occupancy. Using a semi-experimental approach, we investigated if a commercial, strawberry scented lure increased detection probability and visiting time duration in red fox Vulpes vulpes, and the potential reasons for variation in these parameters. In September 2020, within the Stelvio National Park, central Italian Alps, 32 camera sites were randomly assigned t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Previous studies showed an increase in detection frequency of red foxes and other carnivores due to the presence of scent lures and/or baits ( Buyaskas et al 2020 ; Avrin et al 2021 ; Cozzi et al 2022 ). In our study, we did not find an increase in foxes’ detection frequency when adding anthropogenic food to the bin.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed an increase in detection frequency of red foxes and other carnivores due to the presence of scent lures and/or baits ( Buyaskas et al 2020 ; Avrin et al 2021 ; Cozzi et al 2022 ). In our study, we did not find an increase in foxes’ detection frequency when adding anthropogenic food to the bin.…”
Section: Discussionmentioning
confidence: 99%